Regional health integration and cooperation in the Philippines - Valerie Gilbert T. Ulep; Lyle Daryll D. Casas (Philippine Institute for Development Studies (PIDS), 2021)
This paper has two objectives: (1) assess the health sector performance of the Philippines relative to other ASEAN member states and (2) assess regional health integration and cooperation in the Philippines and identify challenges and opportunities. The Philippines is lagging in critical health outcome and access indicators in the region. This is a reflection of the long-standing challenges in terms of health financing, health service delivery, governance, and health human resources. Health integration and cooperation could be instrumental in achieving health system goals. While the country has made significant stride in facilitating regional integration and cooperation in recent years, challenges related to regulations, infrastructure, and implementation remain.
Keywords: 330; regional integration; cooperation; ASEAN; Philippines